Psychological features of behavior and life quality of post-stroke patients - Востротін, Олександр (Psychosomatic Medicine and General Practice, 2023)
These graphic materials are a poster presentation for the III Congress with international participation "Psychosomatic Medicine: science and practice". Which took place on April 21-23, 2023 in Kyiv on the Mediamed portal.